Malaysian Universities Rise In 'Times' Rankings - New Straits Times, Jennifer Gonez & Irdiani Mohd Salleh (2008)
Malaysian universities improved their standings, but none joined High top 200 list of the Times High Education - QS Quacquarelli Symonds World University ranking for 2008